АФОРИСТИЧНІСТЬ МОВИ АХІЛЛА ТАТІЯ - Chakal (Makar), Inesa (Видавництво Національного університету „Острозька академія”, 2016)
The article deals with aphoristic language of the ancient Greek novel “Leucippe and Clitophon”, written by Achilles Tatius (2nd century AD). Linguistic evidences demontrate the semantic fields around the lexical items which sygnalize the aphoristical expressions. The numerous groups of aphorisms belong to the category of nouns, describing the parts of body, location, emotions and abstract notions. We took into consideration the most typical narrative techniques and figures of speech in furtherance of the aphorisms. Antithesis, hyperbole, parallelism, comparison belong to the typical figures of speech. They help to express the contest, submitting it in a concise style. However, sometimes the aphorisms reach more complicated structures due to the combination of two or more stylistic figures. We analysed the functions of the aphorisms in the text in order to approach the author’s linguistic techniques. The classification determines the interconnectedness of didactic (to warn and to teach the audience a moral lesson), cognitive (to understand a philosophical conseption of the human being), interpretive (to estimate and to comment on the specific situation), polemic (building and strengthening arguments in the dispute) and comic functions of aphorism. У статті досліджено афористичність мови давньогрецького роману Ахілла Татія „Левкіппа і Клітофонт” (ІІ ст. н.е.). Виокремлено семантичні поля зорганізовані навколо лексичних одиниць – стрижнів афористичних висловів. Розглянуто найхарактерніші художні та стилістичні фігури, що входять до складу афоризмів письменника. Проаналізовано різноманітні функції афоризмів як засоби формування авторської мовної картини світу.
Aphoristic utterances of Achilles Tatius’s language
Keywords: афоризм; афористичне висловлення; структурно-семантичні та функціональні особливості афоризмів; давньогрецький роман; Ахілл Татій; aphorism; Achilles Tatius; aphoristic utterance